1979
DOI: 10.1007/bf03179115
|View full text |Cite
|
Sign up to set email alerts
|

Acid phosphatase activity in the Indian apple snail,Pila globosa (Swainson), during aestivation and starvation stress

Abstract: Acid phosphatase activity has been studied in hepatopancreas and foot tissues of the Indian apple snail, Pila globosa (Swainson), with reference to aestiva. tion and starvation. The enzyme activity in the tissues of control snails is higher in hepatopancreas, than in foot. The activity of acid phosphatase increased in hepatopancreas and decreased in foot during starvation while it decreased in both the tissues during aestivation. The significance of these findings is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 5 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…Alkaline phosphatase, which plays a critical role in protein synthesis (Pilo et al, 1972), shell formation (Timmermans, 1969) and other secretory activities (Ibrahim et al, 1974) in gastropods and acid phosphatase, a lysosomal enzyme (Aruna et al, 1979) which plays an important role in catabolism, pathological necrosis, autolysis and phagocytosis (Abou-Donia, 1978) were also inhibited by the different treatments of P. granatum bark and C. indica root and their different combinations.…”
Section: Discussionmentioning
confidence: 94%
“…Alkaline phosphatase, which plays a critical role in protein synthesis (Pilo et al, 1972), shell formation (Timmermans, 1969) and other secretory activities (Ibrahim et al, 1974) in gastropods and acid phosphatase, a lysosomal enzyme (Aruna et al, 1979) which plays an important role in catabolism, pathological necrosis, autolysis and phagocytosis (Abou-Donia, 1978) were also inhibited by the different treatments of P. granatum bark and C. indica root and their different combinations.…”
Section: Discussionmentioning
confidence: 94%
“…19 The in vivo inhibition of LDH activity by sublethal doses of the above treatments indicates that the treatments act on the anaerobic metabolism. Alkaline phosphatase (which plays a critical role in protein synthesis, 20 shell formation 21 and other secretory activities 22 in gastropods) and acid phosphatase (a lysosomal enzyme 23 that plays an important role in catabolism, pathological necrosis, autolysis and phagocytosis 24 ) were also inhibited by treatment with oil of AI, CD, bulb powder of AS, NI and the combinations AS + CD and CD + AI.…”
Section: Discussionmentioning
confidence: 95%
“…The enzyme ALP plays a critical role in protein synthesis [36] and secretary activity [37] is comparatively less inhibited than AChE. Acid phosphatase (ACP), a lysosomal enzyme [38], plays an important role in autolysis and phagocytosis, pathological necrosis, and overall catabolism [8,10,39] was reduced significantly. Earlier, it has been observed that increased activity of ACP causes breakdown of existing protein in L. acuminata [18], but inhibition of ACP activity in this study indicates that it is not used in breakdown of cellular protein.…”
Section: Discussionmentioning
confidence: 99%